STATE ENVIRONMENTAL IDEOLOGY: FROM TSARIST EMPIRE TO SUSTAINABLE RUSSIA - ELENA GLADUN; OLGA ZAKHAROVA (BRICS Law Journal)
The main approach to the relationship between mankind and the natural environment is  sustainable development which has increasingly found its way into the context of environmental  legislation. The efficacy and scope of Russian environmental legislation varied during different  periods throughout the history of the country and depended to a great extent on the state ideology which at the time shaped public opinion and environmental awareness. Russian environmental ideology has proven to be inconsistent and contradictory, because it is based on a dual historical  tradition: a pre-revolutionary and Soviet pattern. Environmental ideology in its historical  perspective has always remained on the periphery of scholarly attention in Russia. This paper is an  analysis of the basic domains of the state environmental ideology with the focus on changes that  happened in the periods of the Great October Socialist Revolution and the 1990s when the country  was transitioning to a new democratic state. The study of the historical peculiarities of the state  environmental ideology can contribute to assessing how much Russia has progressed in achieving efficient legal regulation of environmental use and protection. The hypothesis is that the  difficulties in the transition of the Russian Federation to sustainable development are caused by the failure of the state to form a holistic and efficient environmental ideology that can serve as an  adequate background for the development and implementation of legal norms.